ASEAN+3 bond market guide 2016 : Malaysia (ASEAN+3 bond market guide 2016 : Malaysia, 2016)
Cover – Title – Copyright – Contents – Tables, Figures, and Boxes – Tables – 2.1 Examples of Securities Market Legislation by Legislative Tier – 2.2 Regulatory Processes by Issuer Type – 3.1 Segmentation of the Market-Outstanding Value by Type of Bond, Note, or Sukuk – 3.2 Segmentation of the Market-Outstanding Value by Type of Issuer – 3.3 Categories of Principal Advisers and Types of Corporate Proposals – 4.1 Bursa Malaysia Securities Trading Hours – 6.1 Duties and Taxes on Debt Securities and Sukuk in Malaysia – A1 Group of Thirty ComplianceA2.1 Guidelines and Practice and Other Notes-Securities Commission Malaysia – A2.2 Guidelines and Practice and Other Notes-Bank Negara Malaysia and MyClear – Figures – 1.1 Local Currency Bond Issuance in Malaysia, 2015-Conventional versus Sukuk – 1.2 Local Currency Bonds Outstanding in Malaysia – 2.1 Regulatory Process Map-Overview – 3.1 Change in Composition of Government Issuances, 2015-2019 – 3.2 Fully Automated System for Issuing/Tendering Website- Sample Announcement – 3.3 Bond Pricing Agency Malaysia Homepage – 4.1 Fully Automated System for Issuing/Tendering Homepage4.2 Electronic Trading Platform Business Infrastructure – 4.3 Electronic Trading Platform Trading and Reporting Hours – 4.4 Exchange-Traded Bonds and Sukuk Trading Hours – 4.5 Bond Info Hub Website-Intraday Trades Summary – 4.6 Bond Info Hub Homepage – 4.7 Fully Automated System for Issuing/Tendering-Government Bond Yield Curve – 4.8 Bond Info Hub Website-Government Bond Yield Curve – 4.9 Bond Pricing Agency Malaysia Website-Bond Yields in Malaysia – 4.10 Malaysia Islamic Financial Centre Website-Thomson Reuters Bond Pricing Agency Malaysia Sukuk Index4.11 Bond Info Hub Website-Repo Summary – 4.12 Bursa Malaysia Derivatives Website-Malaysian Government Securities Futures – Boxes – 2.1 Securities Commission Malaysia's Lodge and Launch Framework Regulations – 2.2 Securities Commission Malaysia's Regulatory Framework for Bonds – 10.1 Bursa Malaysia Securities Introduces Rule to Facilitate Exchange-Traded Bonds and Sukuk – Foreword – Acknowledgments – Abbreviations – I. Overview – A. Introduction – B. Capital Market Masterplan II, 2011-2020 – C. Regional Cooperation – II. Legal and Regulatory Framework – A. Legal TraditionB. English Translation – C. Legislative Structure – D. Malaysian Bond and Sukuk Market Regulatory Structure – E. Regulatory Framework for Debt Securities and Sukuk – F. Debt Securities and Sukuk Issuance Regulatory Processes – G. Continuous Disclosure Requirements in the Malaysian Market – H. Self-Regulatory Organizations in the Malaysian Market – I. Financial Markets Association Rules Related to Certification and Trading Conventions – J. Bursa Malaysia Rules Related to Bond and Sukuk Listing, Disclosure, and Trading – K. Market Entry Requirements (Nonresidents)L. Market Exit Requirements (Nonresidents)